Does Agricultural Performance Contribute to Rural Poverty Reduction in Indonesia? - Arham, Muhammad Amir; fadhli, Ahmad; Dai, Sri Indriyani (Universitas Negeri Semarang, 2020)
Agriculture is the primary sector in many provinces in Indonesia. In fact, most of the rural communities work in the agricultural sector. Nevertheless, the poverty level in rural areas remains high. Therefore, this study was aimed at investigating the performance of the agricultural sector in reducing the rural poverty level in Indonesia, and to investigate factors that contribute as a determinant in reducing rural poverty level in Indonesia. This study was significant, considering that the result was to contribute to government policy evaluation in the agricultural sector, especially in reducing poverty in rural areas. This study used quantitative analysis through multiple regressions with data panel from 2014 to 2017 from 33 provinces in Indonesia. This study revealed that the increase of agricultural sector share and the widening of the income distribution had caused an increase in poor people in a rural area. This finding also revealed that the income distribution gap was a determinant to the severity of rural poverty. The growth in the agricultural sector to contribute toward the economy could reduce rural poverty level in Indonesia. Meanwhile, agricultural financing, economic growth, inflation, and the farmer exchange rate had not significantly contributed to reducing the poverty level.